Sustained Consumption of a Decaffeinated Green Coffee Nutraceutical Has Limited Effects on Phenolic Metabolism and Bioavailability in Overweight/Obese Subjects - Seguido, Miguel Ángel; Tarradas, Rosa Maria; González-Rámila, Susana; García-Cordero, Joaquín; Sarriá, Beatriz; Bravo-Clemente, Laura; Mateos, Raquel (Nutrients, 2022)
Knowledge on the bioavailability of coffee (poly)phenols mostly come from single dose postprandial studies. This study aimed at investigating the effects of regularly consuming a green coffee phenolic extract (GCPE) on the bioavailability and metabolism of (poly)phenols. Volunteers with overweight/obesity consumed a decaffeinated GCPE nutraceutical containing 300 mg hydroxycinnamates twice daily for two months. Plasma and urinary pharmacokinetics, and fecal excretion of phenolic metabolites were characterized by LC-MS-QToF at weeks 0 and 8. Fifty-four metabolites were identified in biological fluids. Regular consumption of the nutraceutical produced certain changes: reduced forms of caffeic, ferulic and coumaric acids in urine or 3-(3′-hydroxypenyl)propanoic, and 3,4-dihydroxybenzoic acids in feces significantly increased (p < 0.05) after 8 weeks; in contrast, coumaroylquinic and dihydrocoumaroylquinic acids in urine decreased (p < 0.05) compared to baseline excretion. The sum of intestinal and colonic metabolites increased after sustained consumption of GCPE, without reaching statistical significance, suggesting a small overall effect on (poly)phenols’ bioavailability.